Sucessão de macroinvertebrados na decomposição da planta aquática exótica Hydrilla verticillata e da nativa Egeria najas. - Machado, Saulo Bemhur (2019)
Decomposition is a process of great importance to the ecosystem. Macroinvertebrates together with fungi and bacteria play a very important role in the cycling of organic matter. Through decomposition, nutrients that make up the organisms can be reused and macroinvertebrates act by fractionating the organic matter in this process. The exotic species Hydrilla verticillata (L.f) Royle usually causes problems in various regions of the globe such as economic damage in hydroelectric plants. This exotic species competes with native species and can facilitates new invasions. The objective of the present work is to evaluate how the colonization of macroinvertebrates occurs during the decomposition of H. verticillata and E. najas macrophytes, as well as other community attributes during the process such as density, richness, Shannon diversity and Pielou evenness. The experiment was carried out in Garças Lake and the macrophytes were collected in Paraná River. Macrophytes were dried at room temperature and 5 g of each species were added in two types of litterbags, one thin mesh (0.5 mm) and another with thick mesh (4 mm), totalling 100 litterbags. The litterbags were fixed at 5 points in the lake and removed each 4 days. In the laboratory the litterbags were washed with a 0.2 μm mesh sieve, the decomposing material was sorted and the remainder was oven dried for further decay calculation. There was no significant difference in community attributes, except when time was applied assigned to analysis. The decomposition was similar in both species because both had similar characteristics, including phylogenetic proximity. The most observed taxon during the process was Chironomidae. Thus, it is worth noting that more studies are needed to elucidate questions related to the colonization process and quantify the degradation of organic matter of exotic and native species in the Upper Paraná River floodplain.